A CASE FOR THE INCLUSION OF VISUAL THINKING UNITS ACROSS THE ACADEMIC SECTOR - Newcombe, Adam (European Scientific Journal, ESJ, 2014)
This paper argues for the re-introduction of drawing across the university sector. It also posits that modern university education is too limited in the its educational reach across intelligences, focused as it is on textural and logical-mathematical systems of assessment, communication, unit coursework and expected outcomes. The argument for the re-introduction of drawing is also a call for the development, use and study of studio-based education in the tertiary sector. The skills and knowledge acquired in a studio are particularly pertinent to scientific study; being a range of skills and knowledge too often neglected, through the over-use and reliance on digital technology. It must always be remembered that undergraduate students, by and large, are young, often naive and have limited physical, hand,-eye, visual or intrapersonal skills or experience. That is not to say they are unintelligent, but their experience and knowledge is limited, a lack of knowledge and understandings too often forgotten by course writers. Students come to university to learn, but the academy is still caught up in presenting information, a commodity easily acquired in the present on-line, globalized climate. What students lack are observational and spatial skills, analytical and comprehension skills, hand-eye and visual intelligence and knowledge and the ability to communicate verbally and visually, outside of the realms of the computer. Drawing and studio work are both focused on the utilization of multi-intelligence learning. If drawing and studio work were re-introduced into the general tertiary curricula then universities would be graduating much more rounded, more broadly educated and more adaptable graduates and in the end, better scientists.